What do we mean by Climate Services? - Tall, Arame (2013)
Climate services are essential for adaptation to climate variability and change. The endorsement of the Global Framework for Climate Services (GFCS), whose intent is “to strengthen the production, availability, delivery and application of science-based climate prediction and services,” by 155 nations at the 2009 World Climate Conference-III attests to this. The Global Framework aims to bridge the gap between the climate information being developed by scientists and service providers and the practical needs of end-users.1 The GFCS implementation plan targets gaps in climate services in support of our initial climate-sensitive sectors – agriculture, health, disaster reduction and water –especially for those most vulnerable.This will be achieved through the development and incorporation of science-based climate information and predictions into planning, policy and practical decision-making. Effective climate services will facilitate climate-smart decisions that will, for example, mitigate the impacts of climate-related disasters, improve food security and health outcomes, enhance water resources management, and bring better outcomes in disaster risk reduction. As climate services continue to rise in prominence on national, regional and global agendas for climate adaptation and mitigation, it is important to re-examine what is meant by climate services and to look at the more difficult challenge.